PERAN SERTA MASYARAKAT DALAM PENDIDIKAN (Kajian Pada Sekolah Menengah: SMPN 1 Malang, SMPN 10 Malang, SMP Plus Al Kautsar) - Bustanul Arifin; Arif Dermawan; Irsan Habsyi (Pusat Riset dan Inovasi Nasional, 2022)
Education is the responsibility of all components of the nation: schools, parents, society, and government. The factors that determine the success of education are the education carried out by parents and the environment. The conclusions of this study are: obstacles in increasing community participation include environmental factors and parents. The pattern of the relationship between the community and parents in terms of finance, academics, and evaluation. Strategies to increase community participation can be carried out by: revitalizing the role of committees, utilizing institutions and social media, and increasing parental education.